Characterization and expression analysis of somatic embryogenesis receptor kinase (SERK) genes in sexual and apomictic paspalum notatum - Podio, Maricel (2014)
Fil: Podio, Maricel. Universidad Nacional de Rosario. Facultad de Ciencias Agrarias; Argentina.